Psychosocial factors associated with health behaviors in pregnant women of advanced maternal age in Korea - Jeon, Songi; Noh, Wonjung (Frontiers in Public Health, 2023)
Objectives: To determine the association between psychosocial factors and health-promoting and health-impairing behaviors in pregnant women of advanced maternal age (AMA) in Korea. Design: A cross-sectional survey study. Setting: Online survey. Samples: A total of 217 pregnant women aged 35 and older agreed to participate in the study, with 207 participants completing the self-report questionnaires. Methods: We collected self-reported data on demographic, obstetric, and psychosocial factors and prenatal health behaviors using standardized measures. We conducted a descriptive analysis of the collected data and a linear regression to identify significant associations with health-promoting and health-impairing behaviors. Results: We found that maternal–fetal attachment (β = .43, p < .001) and “social atmosphere” of pregnancy stress (β = .13, p = .047) were positively associated with prenatal health-promoting behaviors. We found that artificial conception (β =−.16, p = .011) was negatively associated with prenatal health-impairing behaviors and that multiparity (β = .23, p = .001), and “maternal role” of pregnancy stress (β = .27, p = .003) positively associated with prenatal health-impairing behaviors. Conclusions: Health-impairing behaviors of pregnant AMA women need assessment and the importance of health-promoting behaviors for maternal and infant health need reinforcing. We recommend pregnancy stress assessments at prenatal check-ups and stress relief interventions that consider cultural differences and contexts rather than standardized interventions.